FMD empty capsids combined with the immunostant particle adjuvant -ISPA or ISA206 induce protective immunity against foot and mouth disease virus - Bidart, Juan Esteban (2021)
Foot and Mouth Disease Virus (FMDV) causes economy losses and is controlled by vaccination in many countries. Vaccine formulations based on empty capsids or Virus-Like Particles (VLPs) have the advantage of avoiding the biological hazard of using infectious FMDV, albeit are poorly immunogenic. Recently, we have described that ISPA a new Immune Stimulating Complex adjuvant, is useful to improve the response against FMD of vaccines that use inactivated virus. Now, the adjuvant effects of ISPA and ISA 206 (water/oil/water) on a VLPs-based FMD vaccine were evaluated. VLPs (strain A/Argentina/2001) were obtained in mammalian cell cultures and their elicitation of an immune response against FMDV with and without ISPA or ISA 206 was evaluated in mice as a first approach. Notably, VLPs-ISPA and VLPs-ISA 206 vaccines induced protection against viral challenge in 100 % of mice, while protection induced by VLPs alone was of 40 %. Total and neutralizing FMDV antibodies were higher in the VLPs-ISPA and VLPs-ISA 206 groups compared to the VLPs group. VLPs-ISPA induced significantly higher (p < 0.001) IgG1, IgG2a, IgG2b and IgG3 titers than the VLPs vaccine. Moreover, in comparison with non-adjuvanted VLPs, VLPs-ISPA and VLPs-ISA 206 elicited an increased virus-specific T response, including higher IFNγ+/CD8 + lymphocyte production in mice. When these vaccines were tested in calves, antibody titers reached an Expected Percentage of Protection (EPP) above 90 % in the case of the VLPs-ISPA and VLPs-ISA 206 vaccines, while, in the VLPs group, EPP reached 25 %. IFNγ levels secreted by mononuclear cells of VLP-ISPA-vaccinated cattle were significantly higher than in the VLPs group. Overall, the results demonstrate that VLPs-ISPA or VLPs-ISA 206 are promising formulations for the development of a novel FMD vaccine.